2x+49=-6x+97

Simple and best practice solution for 2x+49=-6x+97 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+49=-6x+97 equation:


Simplifying
2x + 49 = -6x + 97

Reorder the terms:
49 + 2x = -6x + 97

Reorder the terms:
49 + 2x = 97 + -6x

Solving
49 + 2x = 97 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
49 + 2x + 6x = 97 + -6x + 6x

Combine like terms: 2x + 6x = 8x
49 + 8x = 97 + -6x + 6x

Combine like terms: -6x + 6x = 0
49 + 8x = 97 + 0
49 + 8x = 97

Add '-49' to each side of the equation.
49 + -49 + 8x = 97 + -49

Combine like terms: 49 + -49 = 0
0 + 8x = 97 + -49
8x = 97 + -49

Combine like terms: 97 + -49 = 48
8x = 48

Divide each side by '8'.
x = 6

Simplifying
x = 6

See similar equations:

| (2x+4)(6x-8)= | | 8x+70=9x+69 | | 2y-6x=-3 | | 7K+3=K+13 | | 3y-4(-4y-18)=-118 | | 2/3+2=4/3+1/3 | | 19=.8(20x+16)-14x | | 1.05p=31.5 | | 20w+100=280 | | 2d^2+7d=0 | | 6v(2v-3)= | | 4q-72=q+24 | | 13+6z=7(z-1) | | 3(4x-9)=29 | | 4x^3+12x^2+16=0 | | 3c+47=9c+41 | | 4(5)+y=24 | | 100y-2x=0 | | 15b=7b+40 | | 3p-1-2x+9=0 | | 19t+31=2t+65 | | r^2=88 | | 6h+8=26 | | 10y-2x=5 | | -1[7x+6(x+1)]=-4x-6 | | 2y-30=3y-54 | | (11x-25)+(24+10)=90 | | 3+10b-5-4b= | | 3y+8=y+66 | | -48=5c-2 | | 2x^2-13=11 | | 0.12x+1=0.880 |

Equations solver categories